1995
DOI: 10.1016/0092-8674(95)90331-3
|View full text |Cite
|
Sign up to set email alerts
|

The peptide repeat domain of nucleoporin Nup98 functions as a docking site in transport across the nuclear pore complex

Abstract: We report the cDNA deduced primary structure of a wheat germ agglutinin-reactive nuclear pore complex (NPC) protein of rat. The protein, termed Nup98 (for nucleoporin of 98 kDa), contains numerous GLFG and FG repeats and some FXFG repeats and is thus a vertebrate member of a family of GLFG nucleoporins that were previously discovered in yeast. Immunoelectron microscopy showed Nup98 to be asymmetrically located at the nucleoplasmic side of the NPC. Nup98 functions as one of several docking site nucleoporins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
424
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(440 citation statements)
references
References 42 publications
12
424
0
1
Order By: Relevance
“…Over the last decades the pioneering work of Gu¨nter Blobel and colleagues has deciphered the fundamental role of KPNA2 proteins in nuclear protein transport (Radu et al, 1995;Chook and Blobel, 2001). It has further been shown that malfunctions in nuclearcytoplasmic shuttling may contribute to carcinogenesis, for example, of breast and colon (Flamini et al, 1996;Lu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades the pioneering work of Gu¨nter Blobel and colleagues has deciphered the fundamental role of KPNA2 proteins in nuclear protein transport (Radu et al, 1995;Chook and Blobel, 2001). It has further been shown that malfunctions in nuclearcytoplasmic shuttling may contribute to carcinogenesis, for example, of breast and colon (Flamini et al, 1996;Lu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1). At the N-terminal end of each of these appendages are FG-repeat motifs, which are known to function as binding sites for [cargo•transport-factor] complexes (8).…”
Section: Discussionmentioning
confidence: 99%
“…7). Projecting from the scaffold to the center as well as to the cytoplasmic and nucleoplasmic side of the central transport conduit, these FG repeats have a dual function: to capture [cargo•transport-factor] complexes for transport across the central transport conduit (8) and, in an unoccupied state, to also form a permeability barrier (7).…”
mentioning
confidence: 99%
“…In contrast, the FG domains of the Nup62 complex and possibly also Nup98 and POM121 are symmetrically anchored into the inner ring (Fig 1A). Although the exact role of the different types of FG‐Nups has to be further investigated, it has been well established that FG‐Nups interact with the soluble phase of the nuclear transport system thereby enabling active nucleocytoplasmic exchange (Fig 1B; Radu et al , 1995; Strawn et al , 2004). This soluble phase consists of the small GTPase RAN, a number of auxiliary factors as well as nuclear transport receptors (NTRs) that transiently interact with FG‐repeats but also explore the open space of cytoplasm and nucleoplasm to recruit cargos.…”
Section: Introductionmentioning
confidence: 99%